Mechanico-discretionary tools for parity changes - SACCHETTI, U. (PSL Quarterly Review, 2013)
The paper is concerned primarily with the exchange rate, and more specifically with technical criteria for exchange rate adjustments in an international monetary system. Because of the interdependence, however, reference is also made to the domestic adjustment process and the availability of international liquidity. The author assesses the suitability, chiefly from an operational point of view, of clearly defined indicators to serve as guidelines for exchange rate adjustments. The main contention is that indicators serving such a purpose can technically be constructed, but that there are limitations as to their reliability. For this reason, and for the inevitable infringement of national sovereignty which is involved, the role of discretion and judgement, both at the national and international level, is bound to remain important. JEL: E42, F33